PARTISIPASI MASYARAKAT DESA MALASARI DALAM PENGEMBANGAN EKOWISATA TAMAN NASIONAL GUNUNG HALIMUN SALAK (TNGHS) - Fedrina, Rezka (Sekolah Tinggi Pariwisata AMPTA, 2018)
Malasari village is a village located in the Halimun Salak Mountain National Park. During this time the community utilizing national park area for the sake of the livelihood of particularly with regard to forest products. Later in its development with the potential of nature, the tour be an alternative solution for the people of the village of Malasari. The purpose of this research is to know the form of participation by the village of Malasari in the development of Ecotourism Halimun. This research used the qualitative approach with descriptive analytical method. The collection of data using interviews and observations in the field. The data collected was then analysed qualitatively the results showed that the participation of the community of the village of Malasari was formed in 4 stages, namely the participation in decision-making, implementation and utilization as well as evaluation. Based on the results of such research, then there is need for more research on how the level of community participation and efforts for its increase in the ideal pattern of development of ecotourism Village Malasari Keywords: Ecotourism, Participation, National Park